Impact of Typhoon Nanmadol (2011) on the propagation of nonlinear internal waves in the South China Sea - Jeon, Chanhyung; Lee, Kang-Nyeong; Li, Qiang; Park, Jae-Hun (Frontiers in Marine Science, 2024)
In situ measurements from an array of pressure-equipped inverted echo sounders (PIESs), numerical simulation results using a non-hydrostatic model (SUNTANS) that does not account for mesoscale variability, and a ray-tracing method are used to investigate the behavior of nonlinear internal waves (NLIWs) in the South China Sea, focusing on period of Typhoon Nanmadol passage. Unusual significant differences in NLIWs arrival time occur between the PIES observation and SUNTANS simulation results after Typhoon Nanmadol passage; i.e., the observed NLIWs show a delay of 0.5-1.5 h at the westernmost PIES sites compared to the simulated ones in the SUNTANS. A dataassimilated ocean model outputs in addition to satellite altimetry reveal that the passage of Typhoon Nanmadol alters the oceanic environments remarkably, creating thermocline shoaling of 80 m, which can slow down the wave propagation speed. We account for the delay of NLIWs using ray-tracing simulations. Our results demonstrate that typhoon-induced changes in mesoscale structure can significantly impact the fate of NLIWs in the South China Sea, which have potential on ocean mixing and biogeochemical systems.